2006
DOI: 10.1097/01.wnr.0000234749.80936.54
|View full text |Cite
|
Sign up to set email alerts
|

Xylazine promotes axonal regeneration in the crushed optic nerve of adult rats

Abstract: Xylazine, an alpha-2 adrenergic agonist, activates the endogenous trophic factors and neuronal survival signaling. Here, we tested the regenerative effect of xylazine on damaged optic nerve axons in adult rats. After optic nerve crush, xylazine was intraperitoneally injected into three groups of rats: a single administration immediately after the crush, intermittent administration, and daily administration. On day 14, the regenerated axons were quantitatively evaluated by anterograde labeling. Everyday adminis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 14 publications
0
12
0
Order By: Relevance
“…The left ON was then exposed and crushed 2 mm behind the globe with jewelry forceps (Dumont #545, World Precision Instruments, Sarasota, FL, USA) for 10 s, as described previously. 15 Direct ophthalmoloscopy verifi ed that the retinal blood fl ow was not damaged.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The left ON was then exposed and crushed 2 mm behind the globe with jewelry forceps (Dumont #545, World Precision Instruments, Sarasota, FL, USA) for 10 s, as described previously. 15 Direct ophthalmoloscopy verifi ed that the retinal blood fl ow was not damaged.…”
Section: Methodsmentioning
confidence: 99%
“…CTB immunostaining was then performed as described. 15 After blocking, the sections were incubated in a solution of goat anti-CTB antibody (List Biological Laboratories) overnight at 4°C. After washing in PBS, the sections were incubated with a biotinylated rabbit anti-goat IgG antibody (Vector Laboratories, Burlingame, CA, USA) for 2 h at room temperature, followed by 1 : 400 Alexa 488-conjugated streptavidin (Molecular Probes, Eugene, OR, USA).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…After the left optic nerve sheath was exposed, the entire nerve was mechanically crushed 2 mm behind the eye with jewelry forceps (Dumont no. 545, World Precision Instruments, Tokyo, Japan) for 10 seconds as described previously [12], although the tip of the forceps was not seen. Normal retinal circulation was confirmed by ophthalmoscope.…”
Section: Intracellular Calcium Concentrationmentioning
confidence: 99%
“…The superior rectus muscle was incised to expose the left optic nerve, and the left optic nerve was crushed 2 mm behind the eye with forceps for 10 seconds. 18 Care was taken not to occlude the blood vessels and cause retinal ischemia. We confirmed that the retinal circulation was not blocked by indirect ophthalmoscopy and also verified this by demonstrating that the HIF-1a gene was not upregulated by real-time PCR.…”
Section: Optic Nerve Crushmentioning
confidence: 99%